Introduction to Neuromodulation-Based Therapies for Chronic Pain - WU Wen (康复学报)
With the development of an aging population, chronic pain has become a serious public health issue. Long-term drugdependence faces the dilemma of addiction and side effects. Non-drug interventions based on neuromodulation provide new ideas toimprove this situation. Herein, the current status of chronic pain and the limitations of drug therapy are first clarified, highlightingthe need to expand neuromodulation therapies. The mechanism, main methods, and clinical applications of neuromodulation therapyare then discussed in detail. Meanwhile, key indicators for evaluating therapeutic effects are presented, and the strengths and weaknessesof current treatment methods are analyzed. Finally, current issues and challenges of relevant treatment methods are summarized,and possible future research directions are considered, aiming to systematically sort out neuromodulation-based chronic paintreatment strategies and provide references for improving the prognosis and quality of life of patients with chronic pain.